Computational approaches for understanding energy metabolism. (29th July 2013) - Shestov, Alexander A.; Barker, Brandon; Gu, Zhenglong; Locasale, Jason W.
Abstract : There has been a surge of interest in understanding the regulation of metabolic networks involved in disease in recent years. Quantitative models are increasingly being used to interrogate the metabolic pathways that are contained within this complex disease biology. At the core of this effort is the mathematical modeling of central carbon metabolism involving glycolysis and the citric acid cycle (referred to as energy metabolism). Here, we discuss several approaches used to quantitatively model metabolic pathways relating to energy metabolism and discuss their formalisms, successes, and limitations. WIREs Syst Biol Med 2013, 5:733–750. doi: 10.1002/wsbm.1238 This article is categorized under: Analytical and Computational Methods > Computational Methods Models of Systems Properties and Processes > Mechanistic Models Biological Mechanisms > Metabolism